Highly active and durable FexCuyNi1-x-y/FeOOH/NiOOH/CuO complex oxides for oxygen evolution reaction in alkaline media. (1st February 2022) - Wu, Xiaoqiang; Li, Mingming; Li, Qiangguo; Qiao, Liang; Liu, Xiaonan; Lu, Chao; An, Xuguang; Kong, Qingquan; Yao, Weitang; Li, Weiyin; Xiang, Zhiyang; Feng, Wei; et al.
Abstract: Oxygen evolution reaction (OER) catalyzed by Ru/Ir-free electrocatalysts is pivotal for preparing oxygen in efficient way, yet our understanding of the relationship between microphysical properties and OER performance is still insufficient. Here we report on 41 kinds of Fex Cuy Ni1-x-y /FeOOH/NiOOH/CuO complexes (FCN-x) to investigate the Cu and Fe induced electronic perturbation and what it brings to OER performance. As result, the activity mapping of FCN-x shows an optimal composition of 1:2:7 (FCN-7) showing a comparable overpotential potential of 170.3 mV, Tafel slop of 75.9 mV dec −1 and durability of 24 h (∼29% activity loss) to that of mainstream Ru/Ir-free catalysts. Such enhancement could be attributed to the role of alloying contribution of Fe/Cu, electronic perturbation and surface modification of surface oxides. Additionally, the incompletely oxidized Fex Cuy Ni1-x-y not only provide a platform for electron conduction, but also work as a sacrificial material to forming fresh oxides to maintain the content of surface oxides, which is a key driver of the excellent durability of FCN-7. This synthetic strategy may give an effective way to design and screen Ru/Ir-free OER catalysts. Graphical abstract: A platform guideline for designing Fe x Cu y Ni 1-x-y /FeOOH/NiOOH/CuO Complex Oxides is reported . The screened FCN-7 electrocatalysts exhibit not only high OER activity but also superior stability. Its OER performance, and working mechanism is investigated. The FCN-7 with unique composition tuning, species controlling, and electronic structure modification would open up a new avenue for designing high activity and durable Ir-/Ru-free OER catalyst. Image 1 Highlights: 41 kinds of Fex Cuy Ni1-x-y was prepared by the electrodeposition method with accurate composition control. The composition optimization and electron perturbation play a key role on activity modification. There are two optimum compositions existed over 41 kinds of Fex Cuy Ni1-x-y . The Fe0·1 Cu0·2 Ni0.7 showed the best oxygen evolution reaction activity and durability.